Occupational lifting during pregnancy and child’s birth size in a large cohort study - Juhl, Mette; Larsen, Pernille Stemann; Andersen, Per Kragh; Svendsen, Susanne Wulff; Bonde, Jens Peter; Nybo Andersen, Anne-Marie; Strandberg-Larsen, Katrine (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'It has been suggested that the handling of heavy loads during pregnancy is associated with impaired fetal growth. We examined the association between quantity and frequency of maternal occupational lifting and the child’s size at birth, measured by weight, length, ponderal index, small-for-gestational-age (SGA), abdominal circumference, head circumference, and placental weight. ' ' METHODS ': 'We analyzed birth size from the Danish Medical Birth Registry of 66 693 live-born children in the Danish National Birth Cohort according to the mother’s self-reported information on occupational lifting from telephone interviews around gestational week 16. Data were collected in the period 1996–2002. We used linear and logistic regression models and adjusted for confounders. ' ' RESULTS ': 'In the fully adjusted models, most of the mean differences in birth size measures had values indicating a smaller size of offspring among women with occupational lifting versus women with no lifting, but the differences were very small, and there was a statistically significant trend only for placental weight showing lighter weight with increasing number of kilos lifted per day. In jobs likely to include person-lifting, we found increased odds of SGA among children of women who lifted 501–1000 kilos per day [odds ratio (OR) 1.34, 95% confidence interval (95% CI) 0.98–1.83] and >1000 kilos per day (OR 1.51, 95% CI 0.83–2.76) compared to no lifting. In jobs with no person-lifting, occupational lifting was not associated with SGA. ' ' CONCLUSIONS ': 'Overall, we observed no strong support for an association between maternal occupational lifting and impaired size at birth. Our data indicated a potential association between lifting and SGA among offspring of women in occupations that are likely to include person-lifting. These results should, however, be interpreted with caution due to limited statistical power, and we suggest that future studies include detailed, individual information on job functions and ergonomic routines of lifting procedures.
Keywords: antenatal guideline; birth size; birth weight; cohort study; fetal growth; occupational lifting; offspring; pregnancy; work environment